2023
DOI: 10.21203/rs.3.rs-2694774/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of delivery time factor on treatment time and plan quality in tomotherapy

Abstract: Background The delivery time factor (DTF) is a new parameter introduced by the RayStation treatment planning system for tomotherapy treatment planning. This study investigated the effects of this factor on various tomotherapy plans. Methods Overall, 25 patients with cancer (head and neck, 6; lung, 9; prostate, 10) were enrolled in this study. For these patients, helical tomotherapy plans with a field width of 2.5 cm, pitch of 0.287, and DTF of 2.0 were created. All the initial plans were recalculated by chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This could be due to several reasons, including more stringent dose constraints were set and the DTF parameter in A-TOMO plans was set to 1.7, which made the execution time of each rotation approximately 20 seconds. A previous study indicated that increasing the DTF, while improving plan quality, led to longer dose delivery times [37] . Additionally, compared to TOMO plans, VMAT plans had shorter dose delivery times, consistent with previous studies [38] .…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to several reasons, including more stringent dose constraints were set and the DTF parameter in A-TOMO plans was set to 1.7, which made the execution time of each rotation approximately 20 seconds. A previous study indicated that increasing the DTF, while improving plan quality, led to longer dose delivery times [37] . Additionally, compared to TOMO plans, VMAT plans had shorter dose delivery times, consistent with previous studies [38] .…”
Section: Discussionmentioning
confidence: 99%